Psychological Well-Being Profile: Teacher Perception in a Higher Education Institution in the Northwest of the Colombian Caribbean Region: Perfil de bienestar psicológico: percepción docente en una institución de educación superior del noroccidente de la región Caribe colombiana - Mora Aguilar, Efraín; Agudelo Hernández, Felipe; Ureña Villamizar, Yan Carlos; Lozano Ardila, Martha Cecilia; Zapata Molina, Camilo (Gaceta Médica de Caracas, 2026)
Introduction: Structural tensions in higher education affect teachers’ mental health, requiring evidence and demanding analysis situated in contexts of regional asymmetry. Objective: To analyse the psychological well-being profile through the perception of university teachers at a higher education institution in Montería, Colombia. Methods: Cross-sectional observational study with a nested qualitative component (sequential mixed design). Following STROBE guidelines, 61 health sciences faculty members selected through non-probabilistic sampling were included. Ryff’s Psychological Well-being Scale (39 items; 6-point Likert scale) was validated in Colombia, and semi-structured interviews were conducted; four additional participants for the qualitative phase were analysed using a phenomenological-hermeneutic approach to identify emerging experiential categories.